Pemanfaatan Minyak Jelantah Untuk Bahan Baku Lilin Aromaterapi Di Yayasan Al Kahfi Medan - Dalimunthe, Nisaul Fadilah; Muhammad Thoriq Al Fath; Gina Cynthia R. Hasibuan; Tania Alda; Juan Akmal Nasution; Indah Mutya Sari; Janeta Fazriah Rambe; Putri Khodijah; Muhammad Fajar (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
Waste cooking oil or what is commonly known as used cooking oil or Waste Cooking Oil (WCO) is one of the biggest contributors to waste in Indonesia. Waste cooking oil can have a negative impact on health and the environment, so it needs to be recycled into economically valuable products such as soap and candles. Through the results of surveys and FGDs with partners, this community service activity aims to find solutions to the problems faced by partners (Al-Kahfi Medan Foundation), namely the less-than-optimal use of used cooking oil from frying from partners' environments which are surrounded by the homes of residents who process food in the kitchen. So, this service aims to process used cooking oil as raw material for making aromatherapy candles. The object of this research is economically unproductive people, namely children at the Al-Kahfi Foundation in Medan. The used cooking oil is recycled as the main raw material and with the addition of stearic acid and aromatherapy, aromatherapy candles are produced which can be used by partners both for daily needs and for sale as business partners in seeking financial income. The aim of adding aromatherapy is to scent the entire room, thereby creating a comfortable sensation for those who inhale it. So in making it, adequate skills are needed so that they can produce quality products with high selling value by utilizing used cooking oil. The service that has been carried out is going well. Socialization activities accompanied by a direct manufacturing process make partners understand and enthusiastic about participating in this program.